Profile of Amino Acid and Fatty Acid from Different Type of Worm as Feed of Broodstock Candidates for Domesticated Uceng (Nemacheilus fasciatus) - Sholikah, Lik Anatus; Soeprijanto, Agoes; Kilawati, Yuni (Research Journal of Life Science, 2020)
Uceng fish (Nemacheilus fasciatus) is a fish that lives wild on the river. All this time, the people have only relied on fishing from nature to consume, but the high market demand for fish will increase river fishing activities in excess. One of the steps to suppress the decline in fish populations is domestication because currently, the fish is not yet cultivated. The domestication process by feeding worms containing amino acids and fatty acids accelerates broodstock candidates' gonadal development. This research aims to determine the type of worms suitable as feed for the growth and gonadal development of broodstock candidates. The method that used in this research is Completely Randomized Design (CRD) with 3 treatments and 3 repetitions. Based on the analysis of amino acids and fatty acids in each type of worm, the best results were obtained on Lumbricus rubellus with an amino acid content of 50.91 gr/100gr and fatty acid 292.27%.